Comprehension Process in Metacognitive Perspective Among University Students - Othman, Yahya; Mustapha, Ghazali (EDUCARE, 2010)
ABSTRACT: Reading process requires readers to think deeply on the aspects that they have read in order to achieve an effective understanding. The readers need to figure out whether they understand the content that they have read. The ability to comprehend reading text would be the major aim in reading process. For students at tertiary levels, this ability is strongly associated to oneâs field of study. From the stand point of critical and creative thinking skills, especially from the metacognitive aspect, students have different perspective of comprehension. This study is conducted to examine the process opted by Malaysian university students in comprehending text using a qualitative research method. A total of eight respondents following the bachelor in education programme participated in this study. Data was obtained via interviews, document analysis, and classroom observation. The findings indicate that there is a different perspective amongst students with regards to the use of metacognitive in understanding the text. These differences were influenced by the strategies used, the level of text difficulty, types of text and studentsâ perception of the text read.KEY WORDS: comprehend reading text, metacognitive aspect, Malaysian university students, and different perspectives.Â Â Â About the Authors: Dr. Yahya Othman is a Senior Lecturer at the Language and Literacy Academic Goup, Sultan Hassanal Bolkiah Institute of Education UBD (University of Brunei Darussalam), Jalan Tunku Link Gadong BE1410, Negara Brunei Darussalam. Dr. Ghazali Mustapha is a Senior Lecturer at the University of Putra Malaysia (UPM), Serdang, Selangor Darul Ehsan, Malaysia. They can be reached at: yahyaoth@gmail.com and gm@educ.upm.edu.myÂ How to cite this article? Othman, Yahya & Ghazali Mustapha. (2010). âComprehension Process in Metacognitive Perspective Among University Studentsâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.171-184. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 8, 2009); Revised (January 18, 2010); and Published (February 17, 2010).Â